2010
DOI: 10.2119/molmed.2009.00154
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin as a Novel Therapy for Radiation Combined Injury

Abstract: The threat of nuclear terrorism has led to growing worldwide concern about exposure to radiation. Acute radiation syndrome, or radiation sickness, develops after whole-body or a partial-body irradiation with a high dose of radiation. In the terrorist radiation exposure scenario, however, radiation victims likely suffer from additional injuries such as trauma, burns, wounds or sepsis. Thus, high-dose radiation injuries and appropriate therapeutic interventions must be studied. Despite advances in our understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 76 publications
(77 reference statements)
6
38
0
Order By: Relevance
“…These results are consistent with previously reported observations in rats (40, 41), guinea pigs (42), dogs (43), swine (44) and mice (1, 5, 6, 45–48). Consequences of either radiation alone or combined injury include acute myelosuppression, thrombocytopenia, immune system inhibition, fluid imbalance, macro/microcirculation failure, massive cellular damage and disruption of vital organ functions, which lead to multiple organ dysfunction syndrome and multiple organ failure, the most frequent causes of death after irradiation (42–44).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with previously reported observations in rats (40, 41), guinea pigs (42), dogs (43), swine (44) and mice (1, 5, 6, 45–48). Consequences of either radiation alone or combined injury include acute myelosuppression, thrombocytopenia, immune system inhibition, fluid imbalance, macro/microcirculation failure, massive cellular damage and disruption of vital organ functions, which lead to multiple organ dysfunction syndrome and multiple organ failure, the most frequent causes of death after irradiation (42–44).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to the mice subjected to radiation alone, peg-G-CSF failed to improve survival after combined injury with burn. This could be due to the complexity of mechanisms of combined injuries, involving the enhancement of serum cytokines/chemokines and systemic bacterial infection (7, 47, 48), which requires more than peg-G-CSF to manage the imbalance of homeostasis. The G-CSF survival improvement after irradiation alone in our study is consistent with that observed in nonhuman primates (8, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation delayed wound-healing abilities. These results are consistent with previous observations in rats [20, 21], guinea pigs [22], dogs [23], swine [24], and mice [1, 5, 6, 15, 25–27]. Medical sequelae of either RI or CI include acute myelosuppression, immune system inhibition, fluid imbalance, systemic inflammation, macro-/microcirculation failure, massive cellular damage, sepsis, and disruption of vital organ functions, which lead to MOD and MOF, the most frequent causes of death after irradiation [22–24].…”
Section: Discussionsupporting
confidence: 93%
“…An important feature of animals treated with ghrelin was the lower degree of hepatocellular injury, highlighted by dedicated experiments using an acute toxic model of liver injury. The ability of ghrelin to counteract tissue damage is in line with the protective roles reported in other tissues [7,8]. In the liver, ghrelin affected several components of tissue injury, namely inflammation, apoptosis, and generation of oxidative stressrelated molecules (Fig.…”
supporting
confidence: 75%